DETERMINING THE OPTIMAL SHARE PORTFOLIO FOR THE CONSTRUCTION, PHARMACEUTICAL AND MINING SECTORS LISTED ON THE INDONESIA STOCK EXCHANGE USING THE CAPITAL ASSET PRICING MODEL (CAPM) FOR THE 2018 – 2022 PERIOD - Binti Qurotul Aini; Dudi Rudianto (Sean Institute, 2023)
This study aims to determine the optimal portfolio results, the proportion of funds in each stock, as well as to calculate the return and risk of the portfolio in Construction, Pharmaceutical and Mining sector stocks listed on the Indonesia Stock Exchange using the Capital Asset Pricing Model (CAPM). This study uses data on monthly stocks that are consistently listed on the Indonesia Stock Exchange. There are 13 stocks selected for research in the order of the highest shares listed on the Indonesia Stock Exchange with the codes ACST, ADHI, ADRO, BUMI, BYAN, KAEF, KLBF, PTBA, PTPP, SIDO, TSPC, WIKA, WSKT. The data was taken from February 2018 to February 2022. The formation of an optimal stock portfolio using the CAPM shows that there are five stocks that fall into the optimal stock portfolio category and produce a return of 0.166% with a risk level of 0.554%.